(untitled) (Journal of the College of Basic Education, 2023)
In recent years, the world has witnessed remarkable progress in the development of knowledge and related sciences.human beings, which had a significant impact in pushing most societies to introduce radical changes.tangible in its policies, economics, plans, programs and teaching methods in order to keep pace withThis is behind the civilizational and technological progress, and we have to think about the role of man in the world.The future and the weapon required to succeed in his practical life, (Mohamed, 2001, pg. 7).The primary responsibility of the teacher has become to draw an outline of the teaching strategy and teaching aids.to achieve specific goals with his interest in all the elements that affect this strategy such asThe preparation of the classroom and the method of grouping the students, (Al-Tobji, 1988, pg. 37).However, the methods and methods of teaching are still monotonous, so the lectures areNumber of students, which is characterized by rigidity and negativity, and does not make the student the focus of the teaching process.(Ibrahim, 1997, pg. 98).Therefore, the directives took to liberate little by little from this monotonous pattern, looking forward to diversity.In other educational strategies and methods that are directly based on the learner’s taskIn the educational process, as an active participant and participant, he is associated with a group learning action.A positive element that participates in the press debate by analyzing, applying and extracting ideas.meanings and results, (Jassim, 1996, pg.) 3Hence the interest in developing and introducing multiple teaching methods and methods that are more effective.And a product of the traditional methods and methods in which the teacher forms the center of activity in the process.educational and educational, while the student finds the center of activity in modern methods that emphasizeEducation and Developing Their Capabilities, (Al-Khawaldah, 1993, p. 10)